Host status of purple passionfruit for the Mediterranean fruit fly (Diptera: Tephritidae) - Rengifo, JA; García, J.G.; Rodríguez, J.F.; Wyckhuys, Kris A.G. (Florida Entomological Society, 2011)
The Mediterranean fruit fly Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) is a key pest of a wide range of fruit crops and the focus of rigid quarantine restrictions and eradication measures in several countries. In Colombia, the susceptibility of purple passionfruit (Pasiflora edulis f. edulis Sims; Violales: Passifloraceae) to C. capitata is uncertain. Field collections of fruit were made to evaluate natural infestation. Forced infestation studies were conducted in the laboratory with punctured and intact fruit to determine the acceptability of fruit at different stages of maturity and physiological suitability of fruit to development. No C. capitata larvae were found and no adults emerged from a total of 976 hand-picked fruit and 623 fallen fruit. In the meantime, trap data indicated that C. capitata is not present in the principal passionfruit production regions. For intact fruit, C. capitata females oviposited exclusively in fruit of maturity level zero, with 41.67% of fruit accepted for oviposition and an average of 183.1 ± 33.8 eggs per fruit. No oviposition was recorded in fruit of maturity levels 2 and 4. For punctured fruit, C. capitata oviposited a total of 84,410 and 84,250 eggs into fruit of maturity levels 0 and 2, respectively, but no C. capitata adults emerged from fruit at either maturity level. Laboratory tests suggest that purple passionfruit is a non-host for C. capitata.